The effect of tennis batting sound on anxiety: a randomized controlled trial and basic acoustic analysis - Wang, Hao; Zhang, Geng; Li, Xiang; Pu, Shihong (Frontiers in Psychology, 2023)
Purpose: To investigate the potential role of the unique sound of tennis in alleviating anxiety. Previous research has consistently shown that exercise can mitigate anxiety, primarily attributed to the impact of increased physical activity on hormonal and neurostructural changes. However, in daily life we find that one of the reasons people are drawn to tennis is its distinctive sound. In this study, we specifically examined the influence of this sound on anxiety. Methods and Results: In a randomized controlled experiment involving 96 participants reporting chronic anxiety (n 1 = n 2 = 48), we found that the control group exhibited an average reduction of 0.00156 in anxiety scores four weeks before and after the study. On the other hand, the experimental group, exposed to tennis stroke sound stimuli, showed an average reduction of 0.02896 in anxiety scores after four weeks, with some individuals even experiencing a decrease from anxiety to mild anxiety. Furthermore, the analysis of sound data revealed that the sound of tennis exhibited a pleasing timbre, with the primary sound frequencies ranging from 100 to 2800Hz. The rhythm of the sound had an average interval of approximately 1.758″ (± 0.41), corresponding to speed of approximately 93.6 km/h. The sound exhibited a steady rhythm, orderly variations in pitch, and a soothing timbre. Conclusion: This study confirms that the sound of tennis alone contributes to anxiety relief, attributed to its suitable loudness, steady rhythm, and orderly variations in pitch, all of which align with human auditory characteristics. This indicates that a considerable portion of the anxiety-alleviating effects of tennis attributed to its comforting sound.